Analisa Pengaruh Perubahan Harga Emas, Suku Bunga Penjaminan dan Kurs Valas Rupiah Atas Dolar Terhadap Indeks Harga Saham Gabungan Periode 2013-2018 - I Ketut Kusuma Wijaya (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2019)
Investment is an activity to manage assets and assets so that assets or assets can provide results in the future. This investment is important because of inflation. Inflation will always be in developing countries like Indonesia, where the economy is still experiencing growth. Broadly speaking, investment is divided into two, namely investment in the real sector and investment in the financial sector. Real investment in the form of property purchases, factory construction, trade in goods and commodities. (for example, produce, mining). While investment in the financial sector such as the capital market (stocks, bond purchases, sukuk, derivatives and mutual funds), the forex market and deposits in banks (deposits, savings and current accounts). This study aims to determine the effect of changes in gold prices, guaranteed interest rates and the exchange rate of the US dollar against the Indonesian Stock Exchange Composite Index. The analytical tool used is multiple linear regression and hypothesis testing is done by partial test (T-test) and simultaneous test (F-Test) and standardized coefficient test.